2023
DOI: 10.1002/jbmr.4825
|View full text |Cite
|
Sign up to set email alerts
|

Jump Power Predicts Fracture Risk in Older Adults Independent of Sarcopenia and FRAX

Abstract: Low countermovement jump power is associated with prevalent fracture, osteoporosis, and sarcopenia in older adults. However, whether jump power predicts incident fracture risk remains uninvestigated. Data of 1366 older adults in a prospective community cohort were analyzed. Jump power was measured using a computerized ground force plate system. Fracture events were ascertained by follow‐up interview and linkage to the national claim database (median follow‐up 6.4 years). Participants were divided into normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In the studies of older adults in humans, impairment of countermovement jump power was observed at earlier time points compared to other measures of physical performance such as timed get-up-and-go test, chair rise test, or muscle force measures such as handgrip strength 12 , 22 , 23 . Jump power assessment improved fracture risk prediction when added to conventional measures of physical performance and muscle strength by detecting individuals who have impaired physical performance at an earlier stage 24 . These findings, which indicate the value of jump power measurement as a sensitive biomarker of age-related changes in physical performance, can be translated as the potential advantage of countermovement jump power assessment in rodent models of aging and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of older adults in humans, impairment of countermovement jump power was observed at earlier time points compared to other measures of physical performance such as timed get-up-and-go test, chair rise test, or muscle force measures such as handgrip strength 12 , 22 , 23 . Jump power assessment improved fracture risk prediction when added to conventional measures of physical performance and muscle strength by detecting individuals who have impaired physical performance at an earlier stage 24 . These findings, which indicate the value of jump power measurement as a sensitive biomarker of age-related changes in physical performance, can be translated as the potential advantage of countermovement jump power assessment in rodent models of aging and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Before testing, participants maintained an upright standing position, with feet parallel to each other at shoulder width and hands placed on the hips. On the signal “Go!”, participants flexed their knees at approximately 90° and jumped as high as possible [ 11 , 12 , 13 , 14 ]. No specific recommendations were provided to indicate hip position during the CMJ, given that this approach is not commonly used in the literature [ 11 , 12 , 13 , 14 ] and that older adults might require different hip adequations to stand up [ 24 ] according to their physical limitations.…”
Section: Methodsmentioning
confidence: 99%
“…On the signal "Go! ", participants flexed their knees at approximately 90 • and jumped as high as possible [11][12][13][14]. No specific recommendations were provided to indicate hip position during the CMJ, given that this approach is not commonly used in the literature [11][12][13][14] and that older adults might require different hip adequations to stand up [24] according to their physical limitations.…”
Section: Countermovement Jumpmentioning
confidence: 99%
See 1 more Smart Citation